Failure Mechanism and Control Technology of Thick and Soft Coal Fully Mechanized Caving Roadway under Double Gobs in Close Coal Seams - Shengrong Xie; Xiaoyu Wu; Dongdong Chen; Yaohui Sun; En Wang; Xiaowei Wu; Xiaobo Duan; Zaisheng Jiang; Pengyu Qi; Songhao Shi (Shock and Vibration)
The surrounding rock of the roadway under double gobs in the lower coal seams is partially damaged by the mining of the upper coal seam and the stress superimposition of the stepped coal pillars. What is worse, the upper layer of the roof is collapse gangue in double gobs, which makes the anchor cable unable to anchor the reliable bearing layer, so the anchoring performance is weakened. The actual drawing forces of the anchor bolt and anchor cable are only approximately 50 kN and 80 kN, respectively. The roadway develops cracks and large deformations with increasing difficulty in achieving safe ventilation. In view of the above problems, taking the close coal seam mining in the Zhengwen Coal Mine as the engineering background, a theoretical calculation is used to obtain the loading of the step coal pillars and the slip line field distribution of the floor depth. The numerical simulation monitors the stress superimposition of stepped coal pillars and the distribution of elastoplastic areas to effectively evaluate the layout of mining roadways. The numerical simulation also analyzes the effective prestress field distribution of the broken roof and grouting roof anchor cable. A laboratory test was used to monitor the strength of the grouting test block of the broken coal body. Then, we proposed that grouting anchor cable be used to strengthen the weak surface of the roof and block the roof cracks. From on-site measurement, the roadway was seen to be arranged in the lateral stress stabilization area of the stepped coal pillars, the combined support technology of the grouting anchor cable (bolt) + U type steel + a single prop was adopted, the roadway deformation was small, the gas influx was reduced, and the drawing force of the anchor bolt and the anchor cable was increased to approximately 160 kN and 350 kN, respectively. The overall design and control technology of the roadway can meet the site safety and efficient production requirements.